2014
DOI: 10.1589/jpts.26.1247
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationships between the Psychological Acceptance Process of Athletic Injury and Athletic Rehabilitation Behavior

Abstract: [Purpose] The purpose of this study was to examine the causal relationships between the psychological acceptance process of athletic injury and athletic-rehabilitation behavior. [Subjects] One hundred forty-four athletes who had injury experiences participated in this study, and 133 (mean age = 20.21 years, SD = 1.07; mean weeks without playing sports = 7.97 weeks, SD = 11.26) of them provided valid questionnaire responses which were subjected to analysis. [Methods] The subjects were asked to answer our origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Previous studies (McDonald & Hardy, 1990;Nakagomi & Uemukai, 1994;Tatsumi & Nakagomi, 1999) have indicated a positive correlation between AIPA and dedication to rehabilitation. Uemukai (1993), Tatsumi (2013), Tatsumi and Takenouchi (2014) quantitatively demonstrated this correlation. Moreo-ver, Tatsumi (2012) indicateda positive correlation between AIPA during rehabilitation and cognition of recovery of athletic movements, as well as the sense of self-development when returning to sports.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Previous studies (McDonald & Hardy, 1990;Nakagomi & Uemukai, 1994;Tatsumi & Nakagomi, 1999) have indicated a positive correlation between AIPA and dedication to rehabilitation. Uemukai (1993), Tatsumi (2013), Tatsumi and Takenouchi (2014) quantitatively demonstrated this correlation. Moreo-ver, Tatsumi (2012) indicateda positive correlation between AIPA during rehabilitation and cognition of recovery of athletic movements, as well as the sense of self-development when returning to sports.…”
Section: Introductionmentioning
confidence: 76%
“…The degree of recovery of emotional stability and time perspective was measured using the Emotional Stability scale and Time Perspective scale, sub-scales of the Psycho-Social Recovery Factor Scale (PSRF-S) developed by Tatsumi and Takenouchi (2014). We adopted four items that showed higher factor loadings from each scale, in total eight items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of a previous study demonstrated a positive relationship between athletic injury psychological acceptance (AIPA) and rehabilitation behaviors. They pointed out the effectiveness of psychological support aimed at acceptance of an injury 1 , 2 , 3 , 4 ) . However, to get a clear view of appropriate goals and tasks to support injured athletes, it is essential to examine their adaptive state after returning to competition instead of targeting short-term intervention effects, such as psychological stress reduction and devotion to rehabilitation behaviors.…”
Section: Introductionmentioning
confidence: 99%